Enteral feeding during indomethacin and ibuprofen treatment of a patent ductus arteriosus - Clyman, Ronald (2013)
OBJECTIVE: To test the hypothesis that infants who are just being introduced to enteral feedings will advance to full enteral nutrition at a faster rate if they receive “trophic” (15 ml/kg/day) enteral feedings while receiving indomethacin or ibuprofen treatment for patent ductus arteriosus (PDA). STUDY DESIGN: Infants were eligible for the study if they were 23(1/7) – 30(6/7) weeks gestation, weighed 401–1250 g at birth, received maximum enteral volumes ≤60 ml/kg/day and were about to be treated with indomethacin or ibuprofen. A standardized “feeding advance regimen” and guidelines for managing feeding intolerance were followed at each site (n=13). RESULTS: Infants (n=177; 26.3±1.9 wks (±SD) gestation) were randomized at 6.5±3.9 days to receive “trophic” feeds (“feeding” group, n=81: indomethacin=80%, ibuprofen=20%) or no feeds (“fasting (npo)” group, n=96: indomethacin=75%, ibuprofen=25%) during the drug administration period. Maximum daily enteral volumes prior to study entry were 14±15 ml/kg/day. After drug treatment, infants randomized to the “feeding” arm required fewer days to reach the study’s feeding volume endpoint (120 ml/kg/day). Although the enteral feeding endpoint was reached at an earlier postnatal age, the age at which central venous lines were removed did not differ between the two groups. There were no differences between the two groups in the incidence of infection, necrotizing enterocolitis, spontaneous intestinal perforation or other neonatal morbidities. CONCLUSION: Infants required less time to reach the feeding volume endpoint if they were given “trophic” enteral feedings when they received indomethacin or ibuprofen treatments.